Pertanggungjawaban Hukum Terjadinya Kecelakaan dalam Belajar Mengemudi - I Wayan Dandy Astrawan; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Motorized vehicles, both motorbikes and cars, are a means of supporting the mobility of people and goods in order to facilitate community life. This affects the existence of car driving courses in Indonesia which were founded by entrepreneurs. The purpose of this study is to determine the criminal sanctions for the company in the event of an accident in leaming to drive on the highway and the company's civil liability in the event of an accident on the highway. This research uses normative legal research. The results of the study show that criminal sanctions for companies when an accident occurs while leaming to drive are not regulated for the company, but the criminal liability is bome by the student instructor as confirmed in Article 79 paragraphs (1) and (2), Traffic and Road Transport Law. Civil liability to the company in the event of an accident is the obligation to provide assistance to the heirs for the cost of treatment and understanding of the victim if the accident results in death.